Development of bikeway as a strategy for the achievement of sustainable mobility in Barquisimeto (Gaceta Técnica, 2023)
A bikeway design is proposed for the city of Barquisimeto, Venezuela, generating the demand for adequate infrastructures for users of non-motorized modes. Through the participatory and exploratory observation carried out in the section located on Avenida 20, from Avenida Vargas to Avenida Rómulo Gallego, it has 2.59 km, a series of deficiencies were found indicated by cyclists, pedestrians and drivers, expressing the need for a bicycle path, with which the services of parking for bicycles and separators between vehicles and pedestrians can be offered. Being a sustainable solution to the road and environmental problem. Thus, the importance of all the conditioning factors of cyclist mobility was highlighted, for a more refined layout of a cycle path in an urban environment. It was considered an innovative and multifunctional project, projecting that its route be in the area of ​​shops and cultural spaces, adding to the task of minimizing the environmental impact in the center of Barquisimeto
Keywords: bikeway; cycle model furniture; Barquisimeto